Adults With Clinically Meaningful Depressive Symptoms Are More Vulnerable to the Effects of a Pro-inflammatory Diet on Frailty Onset. (7th June 2021) - Millar, Courtney; Dufour, Alyssa; Shivappa, Nitin; Hebert, James; Hannan, Marian; Sahni, Shivani
Abstract: Objectives: The dietary inflammatory index (DII®) reflects the inflammatory potential from dietary intakes. A pro-inflammatory diet (higher DII score) has been linked with frailty and increased risk of depression. It is unclear if depressive symptoms exacerbate the association between a pro-inflammatory diet and frailty. We determined if the association between DII score and frailty differed by depressive symptoms in adults from the Framingham Heart Study (FHS). Methods: This prospective study included non-frail individuals ( n = 1712) with baseline (1998–2001) diet assessment from food frequency questionnaire (FFQ), depressive symptoms from Center for Epidemiologic Studies Depression (CES-D) scale and follow-up frailty measurement (2011–2014). Energy-adjusted DII (E-DII TM ) scores were calculated from foods and nutrients reported on the FFQ. Frailty was defined as fulfilling ≥3 Fried frailty criteria: unintentional weight loss, exhaustion, low physical activity, slow gait speed, and low grip strength. We stratified by baseline CES-D scores <16 or ≥ 16, which denotes the absence or presence of clinically meaningful depressive symptoms, respectively. Logistic regression estimated odds ratios (OR) and 95% confidence intervals (95%CI) for frailty development, adjusting for baseline age, sex, energy intake, current smoking, treatment for diabetes and/or cardiovascular disease, and non-skin cancers. Results: Of the 1712 non-frail individuals at baseline (mean age: 58 ± 8 years, range: 33–81; 45% male), 227 individuals became frail over 16 years. Mean E-DII for all participants was −1.95 ± 2.20 (range: −6.71–5.44). Mean E-DII in frail individuals was −1.73 ± 2.13, while in non-frail individuals it was −1.98 ± 2.21. In those with CES-D < 16, one-unit increase in E-DII (more pro-inflammatory diet) was associated with 16% higher odds (95%CI:1.08–1.26) of frailty. In the cohort who had CES-D ≥16(∼6%), one-unit increase in E-DII was associated with 51% higher odds of frailty (95%CI:1.12–2.03). Conclusions: In this cohort of older adults, those with depressive symptoms had higher odds of frailty with a more inflammatory diet compared to those without. Thus, especially among those with depressive symptoms, addressing the pro-inflammatory diet components may be a useful strategy for reducing or preventing frailty in older adults. Funding Sources: NIA(T32-AG023480)